Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/cbdv.202100493
|View full text |Cite
|
Sign up to set email alerts
|

Computer‐Guided Trypanocidal Activity of Natural Lactones Produced by Endophytic Fungus of Euphorbia umbellata

Abstract: Hundreds of millions of people worldwide are affected by Chagas’ disease caused by Trypanosoma cruzi. Since the current treatment lack efficacy, specificity, and suffers from several side‐effects, novel therapeutics are mandatory. Natural products from endophytic fungi have been useful sources of lead compounds. In this study, three lactones isolated from an endophytic strain culture were in silico evaluated for rational guidance of their bioassay screening. All lactones displayed in vitro activity against T. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 67 publications
(122 reference statements)
0
7
0
Order By: Relevance
“…Different stereoisomers of phomalactone ( F ) were isolated and reported previously from various sources [ 15 , 16 , 17 , 18 ], and some papers did not specify the absolute configuration [ 19 , 20 ], while others assigned the (5 R ,6 R ) absolute configuration to the large positive specific rotation [ 21 ], which was opposite to previous studies [ 15 , 16 , 17 , 18 , 22 ]. In order to determine the absolute configuration of phomalactone independently and unambiguously, we performed TDDFT-ECD, TDDFT-OR, and DFT-VCD studies, which consistently confirmed the (+)- cis -(5 S ,6 S ) absolute configuration (see Supplementary Materials ) [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 86%
“…Different stereoisomers of phomalactone ( F ) were isolated and reported previously from various sources [ 15 , 16 , 17 , 18 ], and some papers did not specify the absolute configuration [ 19 , 20 ], while others assigned the (5 R ,6 R ) absolute configuration to the large positive specific rotation [ 21 ], which was opposite to previous studies [ 15 , 16 , 17 , 18 , 22 ]. In order to determine the absolute configuration of phomalactone independently and unambiguously, we performed TDDFT-ECD, TDDFT-OR, and DFT-VCD studies, which consistently confirmed the (+)- cis -(5 S ,6 S ) absolute configuration (see Supplementary Materials ) [ 23 , 24 ].…”
Section: Resultsmentioning
confidence: 86%
“…(+)-phomalactone 186 (Figure 13), hydroxypestalopyrone 187 (Figure 13), and pestalopyrone 188 (Figure 13) were isolated from the endophytic fungus Aspergillus pseudonomiae J1 cultures and evaluated for in vitro anti-trypanosomal activity against the Trypanosoma cruzi Y strain using an anti-epimastigote assay. Compounds 186-188 showed moderate to weak anti-trypanosomal activities, with IC 50 values of 0.86 µM, 88.33 µM, and 580.19 µM, respectively [99].…”
Section: Lactonesmentioning
confidence: 99%
“…Brassicicenes Q-X 51-58 have been isolated from the phytopathogenic fungus Alternaria brassicicola [99]. Brassicicene S 53 was found to show significant anti-inflammatory activity against the production of NO, TNF-α, and IL-1β at 10 μM.…”
Section: Structural and Biological Diversitymentioning
confidence: 99%
“…A new irlactane-type, irlactin K 255, was isolated from the fermentation broth of the medicinal fungus Irpex lacteus [99]. The absolute configuration of 255 was established by single-crystal X-ray diffraction analysis.…”
Section: Tremulane Sterpurane Phlebiane Merulane and Irlactanementioning
confidence: 99%
See 1 more Smart Citation